STUDI PERILAKU TIANG AKIBAT INTERAKSI STRUKTUR DAN TANAH PADA BANGUNAN GEDUNG - Charles Charles; Hendy Wijaya; Amelia Yuwono (JMTS: Jurnal Mitra Teknik Sipil, 2022)
ABSTRACTThe interaction between pile foundation and soil results a bearing capacity that allows the superstructure to be securely maintained. The interaction impact of the soil structure can lead to more accurate analysis, especially on structure's ability to endure seismic forces. Therefore, the pile foundation must be idealized as a multilinear spring support in order to analyze the interaction of the soil structure. The Midas GTS NX and Midas GEN programs were used to examine the impact of soil structure interactions. The program requires data such as superstructure models, soil factors, pile specifications, and pile bearing capacity. The z-direction deformation (-11,112 mm) and axial force (-2207,914 kN) on the C19-3 pile are both greater than in the corner and edge pile sites under gravity load condition. The z-direction deformation (2,909 mm) and the axial force (587,850 kN) on the C2-2 pile are both greater than in the corner and center pile sites under the x-direction static earthquake load condition. The z-direction deformation (2,909 mm) on the C4-6 pile and the axial force (587,850 kN) on the C4-7 pile are both greater than at the edge and center pile sites under the y-direction static earthquake load condition.ABSTRAKInteraksi antara fondasi tiang dengan tanah menghasilkan daya dukung yang dapat mempertahankan kondisi struktur atas dengan aman. Efek interaksi struktur tanah dapat menghasilkan analisis yang lebih akurat terutama pada kapasitas struktur dalam menahan gaya gempa. Oleh karena itu dalam analisis interaksi struktur tanah, fondasi tiang perlu diidealisasikan sebagai tumpuan pegas multilinear. Analisis efek interaksi struktur tanah dilakukan menggunakan program Midas GTS NX dan Midas GEN. Data yang diperlukan seperti permodelan struktur atas, parameter tanah, spesifikasi tiang, dan daya dukung tiang dimasukkan ke dalam program. Pada kondisi pembebanan gravitasi di tiang C19-3, deformasi arah z (-11,112 mm) dan gaya aksial (-2207,914 kN) kedua nilainya lebih besar daripada di lokasi tiang pojok maupun pinggir. Pada kondisi pembebanan gempa statik arah x di tiang C2-2, deformasi arah z (2,909 mm) dan gaya aksial (587,850 kN) kedua nilainya lebih besar daripada di lokasi tiang pojok maupun tengah. Pada kondisi pembebanan gempa statik arah y, deformasi arah z (2,909 mm) di tiang C4-6 dan gaya aksial (587,850 kN) di tiang C4-7 kedua nilainya lebih besar daripada di lokasi tiang pinggir maupun tengah.